Evaluation of Changes in Intrarenal Oxygenation in Rats Using Multiple Gradient-Recalled Echo (mGRE) Sequence - Priatna, Agus (1999)
Changes in intrarenal oxygenation in rats during pharmacological stimuli were evaluated with a multiple gradient-recalled echo (mGRE) sequence. With administration of the loop diuretic furosemide, oxygenation in the medulla improved; acetazolamide, a proximal tubular diuretic, produced no significant change. These results are consistent with our previous studies in humans and resemble earlier studies of medullary oxygenation using oxygen microelectrodes in anesthetized rats. The technique may be useful in the evaluation of therapeutic strategies in animal models of pathophysiological states such as acute renal failure.